PENGARUH INDIVIDUAL CAPABILITY DAN MOTIVASI TEHADAP KINERJA KARYAWAN PADA PT. BALINDO MANUNGGAL BERSAMA KOTA PALU - Mariani, Ni Made (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
This study aims to determine and analyze simultaneous influence of individual capability and motivation on the performance of employees at PT. Balindo Manunggal Bersama; to analyze partial influence of individual capability and motivation on employees? performance at PT. Balindo Manunggal Bersama. This study uses quantitative approach to explain the relationship between two or more variables studied with a sample of 32 employees. Data analysis technique used is multiple linear regressions. The results of hypothesis testing show that: sig. F value of 0.000 <0.05 means that individual capability and motivation simultaneously have significant influence on employee performance; the value of significance level t sig. 0,000 <? 0.05 shows that individual capability partially has significant influence on employee performance; also, motivation partially has significant influence on employee performance with the significance level of t sig. 0,000 <? 0.05.